Tanggung Jawab Pemerintah Daerah dalam Pemenuhan Ruang Terbuka Hijau pada Area Perkotaan - Surana Mahendra Jati; Mashari Mashari (Prosiding Seminar Nasional Ilmu Hukum, 2024)
The problem currently faced is that the amount of green open space that must be provided by the government has not yet reached 30% of the city area. The problems are as follows: 1) What are the responsibilities of the Semarang City Government in fulfilling green open space in urban areas based on Semarang City Regional Regulation Number 14 of 2011 concerning Semarang City Regional Spatial Planning for 2011-2031 as amended by the Semarang City Regional Regulation Number 5 of 2021? 2) What obstacles does the Semarang City Government face in fulfilling green open space in urban areas? 3) What solutions can the Semarang City Government implement to face obstacles in providing green open space in urban areas? This research uses a normative juridical approach (normative legal research). The data analysis used is a qualitative approach to secondary data as main data and primary data as supporting data. The research results show that the responsibility of the Semarang City Government in fulfilling green open space in urban areas is in accordance with the plan for the distribution of regional service facilities in each part of the city area (BWK). The obstacles faced by the Semarang City Government, namely: juridical obstacles, technical obstacles. Solutions that can be implemented by the Semarang City Government are: enforcing regulations with punishment regarding local building regulations, including the Basic Building Coefficient (KDB) for all buildings so that there is open space in each site which will be useful for planting trees or reforestation, propose an additional budget in the Expenditure Budget Activity Plan (RKAB) according to real needs as well as plans for additional city park development. The proposal for additions outside the routine budget is intended to maximize the implementation of medium and long term work programs. recruiting honorary/contract workers to help with the maintenance of existing city parks.